2020
DOI: 10.1111/dth.14539
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of fractional CO 2 laser in acne scar treatment: A meta‐analysis

Abstract: Fractional CO2 laser is a good option for treating acne scars. However, the clinical efficacy of this treatment modality requires further evidence. To perform a meta‐analysis to assess clinical improvements in acne scars with fractional CO2 laser and non‐CO2 laser therapies. Databases (PubMed, Embase, Cochrane Library) were searched using the search strategy to identify eligible studies. All statistical analyses were performed using the Review Manager 5.0, and a meta‐analysis was conducted to assess the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Different treatment modalities have been under trial for treating them such as chemical peels, laser-assisted resurfacing, dermabrasion and microneedling (MN). However, none of them has proved optimal efficacy and many combinations are still under investigation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different treatment modalities have been under trial for treating them such as chemical peels, laser-assisted resurfacing, dermabrasion and microneedling (MN). However, none of them has proved optimal efficacy and many combinations are still under investigation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse effects of ablative laser treatments were reported, such as prolonged erythema, edema, and post inflammatory hyperpigmentation (PIH). 15 , 16 Wound care after CO 2 laser treatment may cause stress and may affect a patient’s daily activities 17 . Recent clinical studies have also focused on exploring the combination of a CO 2 laser with other therapies, such as PRP and adipose tissue stem cells, to enhance the effectiveness and safety and decrease the incidence of adverse reactions to acne scar treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent studies showed a superiority of efficacy when this procedure is associated with platelet rich plasma (PRP) or Lyophilized-growth factors (L-GFs). 29,30 Regarding photorejuvenation and resurfacing, a recent systemic review of 1093 patients has demonstrated the effectiveness of ablative lasers in several indications, highlighting their superiority if compared to nonablative lasers in the field of resurfacing.…”
Section: Resurfacingmentioning
confidence: 99%
“…Finally, much more rarely, there may be adverse effects such as hypertrophic scarring or infections of the treated site that are often linked more to poor wound management than to treatment. [29][30][31]…”
Section: Side Effectsmentioning
confidence: 99%